2024
DOI: 10.2147/copd.s442725
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Obstructive Pulmonary Disease with Risk of Psychiatric Disorders: A Two-Sample Mendelian Randomization Study

Qinxia Zhang,
Haifu Zhang,
Qinxing Xu

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory disorder often accompanied by comorbidities. Although the past few years have witnessed significant scientific progress, the potential relationship between COPD and mental illness remains a subject of debate. Materials and Methods We retrieved COPD data from the genome-wide association studies (GWAS) directory and data on mental illnesses, including Alzheimer’s disease, schizophrenia, pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Owing to the random allocation of alleles at birth, MR adeptly addresses confounders and reverse causation, which are prevalent challenges in traditional epidemiological studies ( 10 ). Although previous MR studies have suggested that there is no association between COPD and SCZ, these studies were limited to European populations, and no detailed study of confounding and mediating factors was performed, so the results of MR studies of COPD and SCZ are still questionable ( 11 ). Given the complexity and many confounding factors in the pathogenesis of COPD, this study aimed to explore the potential causal relationship between SCZ and COPD using MR analysis to provide new insights and evidence on this important clinical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the random allocation of alleles at birth, MR adeptly addresses confounders and reverse causation, which are prevalent challenges in traditional epidemiological studies ( 10 ). Although previous MR studies have suggested that there is no association between COPD and SCZ, these studies were limited to European populations, and no detailed study of confounding and mediating factors was performed, so the results of MR studies of COPD and SCZ are still questionable ( 11 ). Given the complexity and many confounding factors in the pathogenesis of COPD, this study aimed to explore the potential causal relationship between SCZ and COPD using MR analysis to provide new insights and evidence on this important clinical issue.…”
Section: Introductionmentioning
confidence: 99%